2024
DOI: 10.1021/jasms.3c00419
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Characterization of Synthetic Cannabinoid Metabolite Isomers Using SLIM High-Resolution Ion Mobility-Tandem Mass Spectrometry (HRIM-MS/MS)

Ralph Aderorho,
Shadrack Wilson Lucas,
Christopher D. Chouinard

Abstract: Synthetic cannabinoids, a subclass of new psychoactive substances (NPS), are laboratory-made substances that are chemically similar to those found naturally in the cannabis plant. Many of these substances are illicitly manufactured and have been associated with severe health problems, prompting a need to develop analytical methods capable of characterizing both known and previously undetected compounds. This work focuses on a novel Structures for Lossless Ion Manipulations (SLIM) IM-MS approach to the differen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…SLIM traveling wave (TW) conditions were optimized (frequency and amplitude) for resolving power and signal abundance, by systematically ramping frequency or amplitude while keeping the other parameter constant; this yielded optimized TW conditions of 45 V and 35 000 Hz (Figure S1). SLIM CCS measurements required calibration using the Agilent Tune Mix, as previously, using these specifically optimized TW conditions. , Unlike in those previous studies, where SLIM demonstrated minor, yet easily correctable, SLIM CCS N2 bias (roughly ∼2–3% positive bias for lipids and ∼1% negative bias for synthetic cannabinoid metabolites), these values differed from their matching DT CCS N2 (Table S4) by an average of <0.1% (Table ); all values agreed with their corresponding DT CCS N2 values to within ±0.5%, with the only exception being a previously unresolved peak that will be discussed later. Additionally, the standard deviation of replicate measurements was ±0.2 Å 2 for nearly all compounds.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…SLIM traveling wave (TW) conditions were optimized (frequency and amplitude) for resolving power and signal abundance, by systematically ramping frequency or amplitude while keeping the other parameter constant; this yielded optimized TW conditions of 45 V and 35 000 Hz (Figure S1). SLIM CCS measurements required calibration using the Agilent Tune Mix, as previously, using these specifically optimized TW conditions. , Unlike in those previous studies, where SLIM demonstrated minor, yet easily correctable, SLIM CCS N2 bias (roughly ∼2–3% positive bias for lipids and ∼1% negative bias for synthetic cannabinoid metabolites), these values differed from their matching DT CCS N2 (Table S4) by an average of <0.1% (Table ); all values agreed with their corresponding DT CCS N2 values to within ±0.5%, with the only exception being a previously unresolved peak that will be discussed later. Additionally, the standard deviation of replicate measurements was ±0.2 Å 2 for nearly all compounds.…”
Section: Resultsmentioning
confidence: 91%
“…This recently developed IM technique allows for measurement of mobility as ions are propelled by a traveling wave through serpentine paths patterned on printed circuit boards. The serpentine nature allows for long-path separations (≥13 m) that provide resolving power of R p > 200. Numerous small molecule applications have been demonstrated including separation of isomeric glycans, amino acids and peptides, , bile acids, lipids, , and most recently synthetic cannabinoid metabolites . An important consideration for the proposed coupling of high-resolution IM with quantitative clinical analysis is the anticipated arrival time shift for isotopically labeled internal standards relative to their unlabeled equivalents (i.e., isotopologues), based on differences in their reduced mass. Such separations have been observed previously with SLIM for tetraalkylammonium ions, amino acids, and peptide isotopologues, , as well as with other low-field and high-field IM platforms. Williamson et al used a cyclic IMS (cIMS) device to measure structurally specific mass distribution-based isotopic shifts for 25-hydroxyvitamin D3, among other compounds, and interestingly they determined that the previously identified “closed” and “open” conformations had different relative shifts, with the “closed” showing only a 0.17% relative increase in arrival time in comparison with the 0.28% shift for the “open” conformer .…”
Section: Introductionmentioning
confidence: 82%
“…Our group has reported on a recently commercialized high-resolution IM platform, Structures for Lossless Ion Manipulations (SLIM), 17–19 for the rapid differentiation of synthetic cannabinoid isomers. 20…”
mentioning
confidence: 99%
“…1B). To overcome this challenge, these compounds were derivatized using the common dansyl chloride reaction, 20,21 which selectively dansylated amines and phenolic alcohols. The success of this reaction (which was performed by combining the individual metabolites with dansyl chloride in a pH 9.0 buffer solution maintained at 60 °C for 5 minutes) was monitored by the singly dansylated product at m / z 470.157 (Fig.…”
mentioning
confidence: 99%